2022
DOI: 10.1093/heapol/czac081
|View full text |Cite
|
Sign up to set email alerts
|

Can decreased cost-sharing reduce the vulnerability of sick families to poverty? An analysis of the multi-level social health insurance scheme in China

Abstract: In recent years, China has been increasing social health insurance benefits to alleviate poverty due to illness. In 2015, China introduced the Critical Illness Insurance for patients with high out-of-pocket expenses as supplementary to the social health insurance, which categorised patients with different medical expenses into different cost-sharing policies. We conducted a survey on households with high-cost patients in rural Shandong in 2019 and employed the instrumental variables estimation approach to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Further studies show that participation in medical insurance can stabilize household income (10) and enhance social welfare (14). More importantly, such participation can reduce the likelihood of households falling into poverty due to health risk shocks (1,(15)(16)(17) and the income gap between urban and rural residents (18). Korenman et al (19) developed a healthinclusive poverty measure and found that participation in medical insurance reduced the poverty rate by 2.9 percentage points among people under 65 in Massachusetts and by 3.2 percentage points among children.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Further studies show that participation in medical insurance can stabilize household income (10) and enhance social welfare (14). More importantly, such participation can reduce the likelihood of households falling into poverty due to health risk shocks (1,(15)(16)(17) and the income gap between urban and rural residents (18). Korenman et al (19) developed a healthinclusive poverty measure and found that participation in medical insurance reduced the poverty rate by 2.9 percentage points among people under 65 in Massachusetts and by 3.2 percentage points among children.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…The possibility of disease-induced poverty exists [ 17 ] in China and globally. [ 18 ] According to the office of China’s Poverty Alleviation, 42% of registered poor households lapsed into poverty because of illness in 2017, indicating that disease is a primary cause of rural poverty. [ 19 ] Yang Zhou [ 20 ] showed that 56.3% of poverty was caused by illness among household members, and over 3-fifths of households had at least 1 patient; chronic diseases have long been the largest health challenge for poor rural adults in China.…”
Section: Introductionmentioning
confidence: 99%